2020
DOI: 10.1002/uog.21867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new definitions of pre‐eclampsia on incidence and performance of first‐trimester screening

Abstract: The traditional definition of pre-eclampsia (PE), based on the development of hypertension and proteinuria, has been revised to include cases without proteinuria but with evidence of renal, hepatic or hematological dysfunction. The new definitions of PE resulted in, first, an increase in pregnancies classified as having PE but the additional cases had milder disease, and, second, a non-significant decrease in the performance of first-trimester screening for PE. What are the clinical implications of this work? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 35 publications
3
35
0
2
Order By: Relevance
“…Previous studies of the relationship between PE definitions and outcomes have questioned the value of a broad (vs traditional) definition of PE based on concerns that a low-risk population is being identified by the broad definition, at least at gestational ages preterm. 24,25,27 However, adverse maternal and neonatal outcome rates have been well above the baseline rates, 24,27 similar to our findings, suggesting that the use of a broad definition with uteroplacental function, as defined by EFW, Dopplers, and angiogenic imbalance, is clinically useful. In addition, the independent value of routine maternal laboratory test results and FGR were recently demonstrated 27 ; although the role of headache and visual symptoms was not demonstrated, these have been shown to have prognostic value in the absence of laboratory testing, such as in the self-monitored setting in high-income countries or in low-resource settings where most women and babies die of PE.…”
Section: Comparison With Published Literaturesupporting
confidence: 86%
“…Previous studies of the relationship between PE definitions and outcomes have questioned the value of a broad (vs traditional) definition of PE based on concerns that a low-risk population is being identified by the broad definition, at least at gestational ages preterm. 24,25,27 However, adverse maternal and neonatal outcome rates have been well above the baseline rates, 24,27 similar to our findings, suggesting that the use of a broad definition with uteroplacental function, as defined by EFW, Dopplers, and angiogenic imbalance, is clinically useful. In addition, the independent value of routine maternal laboratory test results and FGR were recently demonstrated 27 ; although the role of headache and visual symptoms was not demonstrated, these have been shown to have prognostic value in the absence of laboratory testing, such as in the self-monitored setting in high-income countries or in low-resource settings where most women and babies die of PE.…”
Section: Comparison With Published Literaturesupporting
confidence: 86%
“…In the first trimester, the competing‐risks approach utilizing maternal factors, MAP, UtA‐PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen‐positive rate, 90% of early‐PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non‐intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively. We have also shown, in a study involving 66 964 pregnancies, that the predictive performance of this approach is similar irrespective of whether PE is defined by the traditional criteria of the International Society for the Study of Hypertension in Pregnancy (ISSHP), which requires the presence of both hypertension and proteinuria, or the new criteria of ISSHP and the American College of Obstetricians and Gynecologists which include cases without proteinuria but with evidence of renal, hepatic or hematological dysfunction.…”
mentioning
confidence: 77%
“…In the first trimester, the competing-risks approach utilizing maternal factors, MAP, UtA-PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen-positive rate, 90% of early-PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non-intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively 32,[45][46][47][48] . We have also shown, in a study involving 66 964 pregnancies, that the predictive performance of this approach is similar irrespective of whether PE is defined by the traditional criteria of the International Society for the Study of Hypertension in Pregnancy (ISSHP), which requires the presence of both hypertension and proteinuria, or the new criteria of ISSHP and the American College of Obstetricians and Gynecologists which include cases without proteinuria but with evidence of renal, hepatic or hematological dysfunction [49][50][51][52] .Fifth, a randomized controlled trial found that aspirin administration after 23 weeks' gestation in a high-risk group identified by second-trimester screening was not effective in preventing PE 53 . In contrast, a more recent randomized trial demonstrated that, in women at high risk of PE, administration of aspirin (150 mg/day) from 11-14 until 36 weeks' gestation reduces the risk of early PE and preterm PE by about 90% and 60%, respectively, and the length of stay in the neonatal intensive care unit by about 70% 54,55 .There is no justification for further delay in the implementation of strategies for prediction and prevention of PE in routine clinical practice.…”
mentioning
confidence: 79%
“…However, this has been shown to have a positive predictive value of just 20% to detect pre-eclampsia-associated complications 56 . The new definition put forward by the ISSHP 55 was shown to increase sensitivity but decrease diagnostic specificity, paralleled by decreased mean severity of outcomes such as gestational age at delivery and birth weight in screen-positive women 57 .…”
Section: Focusing On An Integrated Approach To Tackle Pre-eclampsiamentioning
confidence: 99%